THE ROLE OF PSYCHOLOGICAL FACTORS IN SECOND LANGUAGE LEARNING AND TEACHING - Ahmedova Shohsanam Anvarjon qizi (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract: Second language learning is a complex and multidimensional process influenced not only by linguistic input and instructional methods, but also by a wide range of psychological factors. In recent decades, research in applied linguistics and educational  psychology  has  increasingly  emphasized  the  importance  of  learners’ cognitive, affective, and motivational characteristics in determining success in second language acquisition. This article explores the role of psychological factors in second language learning, with a particular focus on motivation, anxiety, self-confidence, and learner autonomy, which are considered essential components in effective language teaching and learning. Motivation is widely recognized as one of the most influential psychological factors in second language learning. Learners who possess strong intrinsic and extrinsic motivation  tend  to  demonstrate  higher  levels  of  engagement,  persistence,  and achievement. Intrinsic motivation, which stems from personal interest and enjoyment, encourages  learners  to  actively  participate  in  language  activities,  while  extrinsic motivation,  such  as  academic  requirements  or  career  goals,  provides  external reinforcement. This study highlights how teachers can foster motivation by creating supportive  learning  environments,  setting  clear  objectives,  and  incorporating meaningful and communicative tasks into classroom instruction.